2020
DOI: 10.20525/ijrbs.v9i1.591
|View full text |Cite
|
Sign up to set email alerts
|

Perception and prediction of intention to use online banking systems

Abstract: Online banking has become a vital instrument for delivering quality and easily reached banking services at the lowest possible time with ensuring affordability both for customers and service providers. Although this banking has huge potentials and benefits, the successful adoption of online banking remains a significant challenge in the context of an emerging economy like Bangladesh. The purpose of this empirical study is to investigate the factors influencing the online banking services adoption in Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
1
16
0
1
Order By: Relevance
“…Approximately a half of the studies (n = 8) used university students as a sample, followed by studies that considered users of sports applications (n = 4) and other studies took as their general population [54][55][56], a population of sports consumers [45], employees of a sports organization [57] and members of a fitness community [44,58]. Most studies had a higher proportion of females than males (n = 9), followed by studies that had parity in the sample (n = 5), four studies had a higher proportion of males while one study did not indicate the gender distribution of the sample [34]. Finally, all studies except Ha et al [42] and Yoo et al [53] reported some data on the age of the subjects.…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately a half of the studies (n = 8) used university students as a sample, followed by studies that considered users of sports applications (n = 4) and other studies took as their general population [54][55][56], a population of sports consumers [45], employees of a sports organization [57] and members of a fitness community [44,58]. Most studies had a higher proportion of females than males (n = 9), followed by studies that had parity in the sample (n = 5), four studies had a higher proportion of males while one study did not indicate the gender distribution of the sample [34]. Finally, all studies except Ha et al [42] and Yoo et al [53] reported some data on the age of the subjects.…”
Section: Summary Of Reported Intervention Outcomesmentioning
confidence: 99%
“…With regard to other methodological aspects of the studies, it should be noted that all the studies found have had a cross-sectional approach, and no longitudinal study has been found to evaluate the evolution of the subject and his or her real intention to continue using said App. Chen and Lin [34] point out that there may be a discrepancy between the ITU of the App on the part of the consumer and the actual use that they make of this App afterwards. In general, this has been a relationship that some studies have considered [1,35,43]; however, as these are cross-sectional studies, it has not been possible to verify the change that they have had with respect to a lesser or greater use of the App.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive literature on the online banking is based on the Technology Acceptance Model (TAM) (Lee et al, 2003), which was introduced by Davis (1986) for the first time to assess the introduction of information systems into organizations. The approaches based on extended TAM models applied to the online banking industry focused on the following drivers: a) trust; b) usage constraint; c) ease of use; d) accessibility; e) intention to Use (Sikdar et al, 2015); d) perceived usefulness; e) government support; f) risk (Hossain et al, 2020); g) perceived credibility; h) customer awareness; and i) social influence (Lavenjia and Hatammimi, 2015). The case study methodology was also widely used to analyse the evolution of the spread of online banking in general terms regarding security (Hole et al, 2006;Petratos and Faccia, 2019), service quality (Gonzalez et al, 2008;Loonam et O'loughlin, 2008), at a country level application in Saudi Arabia (Al-Somali et Gholami, 2009), in Nigeria (Omonaiye et al, 2015), in Oman (Khalfan et al, 2006), in Malaysia (Tan et al, 2010), in Romania (Guraau, 2002), in Ghana (Perkins and Annan, 2013), in India (Iyengar and Belvalkar, 2009), in Thailand (Nochai and Nochai, 2013), in Finland (Pikkarainen et al, 2006), in China (Hua, 2008), and with regard to specific banks such as Citybank UAE (Al-Mudimigh, 2003), and Saman Bank Iran (Saeednia and Abdollahi, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Several investigations have studied TAM's performance in diverse contexts within developed and developing countries around the world. In previous years, studies on internet banking were conducted in Taiwan (Lee, 2009;Yen & Wu, 2016), India (Hossain et al, 2020), Bangladesh (Kumar Sharma & Madhumohan Govindaluri, 2014), Iran (Yaghoubi & Bahmani, 2010), Pakistan (Haider et al, 2019), Jordan (Rawashdeh, 2015) and UK (McKechnie et al, 2006) among others. Nevertheless, a few studies have focussed on Spanish online banking use through TAM.…”
Section: Technology Acceptance Modelmentioning
confidence: 99%